(untitled) (Global Journals of Research in Engineering, 2024)
This research is to investigate and analyze the reasons behind cost overruns in infrastructure projects compared to the planned costs It also delves into establishing procedures for effectively monitoring and controlling project costs and measuring cost performance indicators throughout the project lifecycle To achieve these goals the research addresses three key questions that provide clarity on the research objectives The research questions primarily focus on the estimation of risk costs for construction and infrastructure projects as an integral part of project knowledge areas Additionally the study analyzes the actual cost estimation methods employed by construction organizations and seeks to develop project cost management as an integrated part of all project knowledge areas thereby enhancing the procedures for monitoring and controlling costs To ensure comprehensive findings the research employs the descriptive statistical analytical approach The quantitative method involves a survey questionnaire administered to 462 respondents while the qualitative approach involves analysis for case studies By utilizing a descriptive approach the research provides an in-depth exploration of the research questions from various perspectives Based on a thorough literature review three research hypotheses were formulated and subsequently validated during the discussion and analysis of the research questions The results of the study affirm the positive validation of these hypotheses The empirical findings reveal the following Accurate study of project costs during the initial stages of the project has a positive impact on controlling cost overruns Effective management of the project risk plan including the identification analysis and control of risks positively contributes to controlling cost overruns The utilization of the Earned Value Management EVM method throughout the project lifecycle serves as a strong indicator that assist in monitoring and controlling project cost overruns In conclusion this research provides valuable insights into the reasons for cost overruns in construction projects and infrastructure It also offers practical procedures for monitoring and controlling project costs as well as essential cost performance indicators throughout the project lifecycle The research findings confirm the importance of managing project risk conducting accurate cost estimations and utilizing effective project management methods to prevent cost overruns